Measurement methods in nasal allergen challenge - Samoliński, Bolesław; Krzych-Fałta, Edyta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Methods for examination of nasal challenge tests: clinical examination – the symptoms to be examined in a challenge test include: itching, sneezing, nasal secretion and the degree of nasal obstruction. Clinical examination can be based on measuring the number of sneezes, the intensity of nasal secretion (the point scale and the visual analogue scale (VAS)); objective measurement technique: Glatzel’s mirror, maximum inspiration measured using the peak nasal inspiratory flow (PNIF) technique, acoustic rhinometry, optical rhinometry, rhinomanometry, and rhinospirography.